The barriers in the implementation of BIM in Malaysia - Tee, Sin Hui (2022)
Building Information Modelling (BIM) is a state-of-the-art technology in the construction industry. The BIM digital platform integrates all the construction information throughout the entire project life cycle to strengthen the efficiency, productivity, and collaboration among the project stakeholders. The Malaysian government has realised the importance of BIM in achieving a sustainable construction industry. In this study, a questionnaire survey was conducted to identify the key barriers that inhibited the readiness of the construction organisations in Malaysia to implement BIM. The data collected from Malaysian stakeholders in the construction industry was analysed using statistical tests such as the Variance Inflation Factor multicollinearity test, Cronbach's alpha reliability test, Kolmogorov-Smirnov normality test, ShapiroWilk normality test, relative importance index test, descriptive statistics, Spearman's correlation analysis, multiple linear regression analysis, and hypothesis testing. The results of these statistical tests proved that the people barrier, policy barrier and technology barrier significantly inhibit the readiness of the construction organisations in Malaysia to implement BIM, whereas the process barrier did not significantly inhibit the readiness of the construction organisations in Malaysia to implement BIM. Overall, the strategies to enhance BIM adoption should be focused on the people barrier, policy barrier and technology barrier instead of the process barrier.